Bernard Wilson and Sharmani Patricia Gabriel (Eds). Asian Children’s Literature and Film in a Global Age: Local, National, and Transnational Trajectories. Singapore: Palgrave Macmillan, 2020. 398 pp. ISBN 978-981-15-2630-5. - Barai, Aneesh (SARE: Southeast Asian Review of English, 2024)
n/a